Probenecid Disrupts a Novel Pannexin 1-Collapsin Response Mediator Protein 2 Interaction and Increases Microtubule Stability - Xu, Xiaoxue; Wicki-Stordeur, Leigh E.; Sanchez-Arias, Juan C.; Liu, Mei; Weaver, Maria S.; Choi, Catherine S. W.; Swayne, Leigh A. (Frontiers in Cellular Neuroscience, 2018)
Neurite formation relies on finely-tuned control of the cytoskeleton. Here we identified a novel protein-protein interaction between the ion and metabolite channel protein Panx1 and collapsin response mediator protein 2 (Crmp2), a positive regulator of microtubule polymerization and stabilization. Panx1 and Crmp2 co-precipitated from both Neuro-2a (N2a) cells and mouse ventricular zone tissue. In vitro binding assays between purified proteins revealed the interaction occurs directly between the Panx1 C-terminus and Crmp2. Because Crmp2 is a well-established microtubule-stabilizing protein, and we previously observed a marked increase in neurite formation following treatment with the Panx1 blocker, probenecid, in N2a cells and ventricular zone neural precursor cells, we investigated the impact of probenecid on the Panx1-Crmp2 interaction. Probenecid treatment significantly disrupted the Panx1-Crmp2 interaction by both immunoprecipitation and proximity ligation analysis, without altering overall Crmp2 protein expression levels. In the presence of probenecid, Crmp2 was concentrated at the distal ends of growing neurites. Moreover, probenecid treatment increased tubulin polymerization and microtubule stability in N2a cells. These results reveal that probenecid disrupts a novel interaction between Panx1 and the microtubule stabilizer, Crmp2, and also increases microtubule stability.